2017
DOI: 10.7759/cureus.1924
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Review of Mandibular Orthognathic Surgeries with a Focus on Intraoral Vertico-sagittal Ramus Osteotomy

Abstract: Severe dentofacial deformities require both orthodontics and surgical management to repair. Modern mandibular orthognathic surgery commonly uses sagittal split ramus osteotomy (SSRO) and intraoral vertical ramus osteotomy (IVRO) methods to treat patients. However, complications like neurosensory disturbances and temporomandibular joint disorders are common following both procedures. In 1992, Choung introduced the intraoral vertico-sagittal ramus osteotomy (IVSRO) which led to a decrease in postoperative compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…Orthognathic surgery is frequently used to treat underlying conditions that affect chewing, facial pain, and aesthetics. 4,13 The patient, in this case, demonstrated significant class III skeletal and mandibula prognathism; of course, the impact of this case was on her appearance, mastication, and speech abnormality. Orthognathic surgery is required in skeletal class III cases with a prognathic mandible, as in this case, it cannot be solved by conventional orthodontic treatment.…”
Section: Discussionmentioning
confidence: 79%
“…Orthognathic surgery is frequently used to treat underlying conditions that affect chewing, facial pain, and aesthetics. 4,13 The patient, in this case, demonstrated significant class III skeletal and mandibula prognathism; of course, the impact of this case was on her appearance, mastication, and speech abnormality. Orthognathic surgery is required in skeletal class III cases with a prognathic mandible, as in this case, it cannot be solved by conventional orthodontic treatment.…”
Section: Discussionmentioning
confidence: 79%
“…This difficulty poses a risk of excessive pressure on the articular disc or an unfavorable condylar position, potentially resulting in joint noise, pain, or exacerbation of pre-existing TMD symptoms. 69 However, Toh and Leung reported that, despite the surgical technique used (IVRO, SSRO, or a combination of the two techniques), 12.5% of patients who were previously asymptomatic developed signs and symptoms after surgery. 62 AlWarawreh et al 71 reported that most patients who underwent SSRO with rigid fixation showed no change in the signs and symptoms of TMD.…”
Section: Discussionmentioning
confidence: 99%
“…The alleviation of TMD symptoms after surgery may be attributed to the absence of fixation between the proximal and distal segments, allowing the proximal segment to attain a stable position. 69 …”
Section: Discussionmentioning
confidence: 99%
“…Neurosensory disturbances reduce the patient satisfaction level by great percentage [ 24 ]. The literature reports that if genioplasty is done alone, the incidence of neurosensory injury is low.…”
Section: Discussionmentioning
confidence: 99%